Políticas públicas culturais: uma avaliação das medidas de enfrentamento aos impactos da Covid-19 no setor cultural em Crateús-Ceará - Sousa, Antonia Hedyvanilde de Oliveira (2024)
This research aims to evaluate the actions carried out by the Department of Culture of the municipality of Crateús-CE, based on the management of the execution of the actions specified by the Aldir Blanc Law, and the impacts of the pandemic period on the cultural sector, with the participation of musicians who participated in the public call through the Notice with resources from the Aldir Blanc Law, National Law 14.017/2020 (of June 29, 2020). The research adopted a qualitative and descriptive approach supported by the evaluative perspective “In-Depth Assessment” (Rodrigues, 2008, 2011). This methodology is essential to capture the nuances of the impacts of public cultural policies, seeking to understand how the Department of Culture ensured the protection and access to culture for the population of Crateús during the Covid-19 health emergency situation. The research techniques include bibliographic review and semi-structured interviews with various actors in the sector. Regarding the methods of analysis, the research prioritized an in-depth understanding of the collected discourses, which not only shed light on the urgent needs of the cultural sector, revealing a detailed overview of the challenges and opportunities faced by the local cultural sector during the COVID-19 pandemic, but also highlighted the importance of emergency cultural public policies to ensure the continuity of artistic activities, while highlighting significant barriers to their access and sustainability. Based on the discussions, suggestions were made for the construction of future cultural public policies. In view of this, the study revealed that, although the Aldir Blanc Law was crucial in mitigating the effects of the crisis on the cultural sector, continuous improvement of cultural public policies is necessary to ensure that they are not only efficient, but also culturally sensitive and adapted to the social context in which they are applied.